Polymorphisms in oxidative stress-related genes and postmenopausal breast cancer risk - Seibold, Petra Beate; Hein, Rebecca; Schmezer, Peter; Hall, Per; Liu, Jianjun; Dahmen, Norbert; Flesch-Janys, Dieter; Popanda, Odilia; Chang-Claude, Jenny (International journal of cancer, 2011)
Breast cancer is the most frequent cancer type among women in western countries. In addition to established risk factors like hormone replacement therapy, oxidative stress may play a role in carcinogenesis through an unbalanced generation of reactive oxygen species that leads to genetic instability. The aim of this study is to assess the influence of common single nucleotide polymorphisms (SNPs) in candidate genes related to oxidative stress on postmenopausal breast cancer risk. We genotyped 109 polymorphisms (mainly tagging SNPs) in 22 candidate genes in 1,639 postmenopausal breast cancer cases and 1,967 controls (set 1) from the German population-based case-control study “MARIE”. SNPs showing association in set 1 were tested in further 863 cases and 2,863 controls from MARIE (set 2) using a joint analysis strategy. Six polymorphisms evaluated in the combined set showed significantly modified breast cancer risk per allele in the joint analysis, including SNPs in CYBA (encoding a subunit of the NADPH oxidase: rs3794624), MT2A (metallothionein 2A: rs1580833), TXN (thioredoxin: rs2301241), and in TXN2 (thioredoxin 2: rs2267337, rs2281082, rs4821494). Associations with the CYBA rs3794624 (OR per allele: 0.93, 95% CI 0.87-0.99) and TXN rs2301241 variants (OR per allele: 1.05, 95% CI 1.00-1.10) were confirmed in the summary risk estimate analysis using up to three additional studies. We found some evidence for association of polymorphisms in genes of the thioredoxin system, CYBA, and MT2A with postmenopausal breast cancer risk. Summary evidence including independent datasets indicated moderate effects in CYBA and TXN that warrant confirmation in large independent studies.